Supervise your kids and beware of water! / Muhammad Wafi A. Rahman ... [et al.] - A. Rahman, Muhammad Wafi; Lamat, Siti Aida; Ahmad, Mohamad Firdaus; Dahlan, Nur Dalilah; Bakri, Nur Hani Syazwani; Syed Mud Puad, Sharifah Maimunah (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2021)
Did you know death caused by drowning among children is the highest in the world? Did you know drowning incidents often occur during school holidays? And did you know which hotspot area of drowning in Malaysia? Based on these questions, we should know the facts of the drowning incident and the preventive measures that need to be taken by every parent so that this drowning incident will not happen to our children. The World Health Organization (WHO, 2021) identified that drowning is among the ten leading causes of death among children and young people (1- 24 years old) in every world region. These incidents are estimated to claim the lives of 236,000 people each year. The Perak Clinical Research Centre study showed that about 500 people, mostly youth, drowned in Malaysia annually, making drowning the second cause of death among those between 1 and 18 years old (Singh et al., 2014). Moreover, a total of 31 children were found drowned in swimming pools and theme parks, with the highest number recorded in Selangor, Kedah, and Pahang, and about 75 percent of the children were under five years old (Audrey, 2017).